A Meta-Analytic Review of the Value of miRNA for Multiple Sclerosis Diagnosis - Zhou, Zongpu; Xiong, Huihui; Xie, Fukang; Wu, Zhongdao; Feng, Ying (Frontiers in Neurology, 2020)
Backgrounds and purpose: Multiple sclerosis (MS) is an immune-mediated chronic inflammatory demyelinating disease of the central nervous system. The etiology of MS is unclear, disease diagnosis mainly based on symptoms and lacks effective laboratory test index. Circulating microRNAs (miRNAs) as sensitive biomarkers have been widely studied, the expression levels of certain miRNAs are dynamically changed in MS patients. This meta-analysis aims to assess the overall diagnostic accuracy of circulating miRNAs for MS. Methods: We searched PubMed, EMBASE, Cochrane Library, CNKI databases as of July 20, 2019. QUADAS was used to assess the quality of included studies. All studies were processed by Stata 15.0 software. 11 articles with 600 patients with MS and 389 controls were included. Results: The sensitivity and specificity, PLR, NLR, and DOR of the overall studies were 0.81 (95 % CI 0.77–0.84), 0.75 (95 % CI 0.68–0.81), 3.3 (95 % CI 2.5–4.3), 0.25 (95 % CI 0.20–0.32), 13 (95 % CI: 8–20), and 0.85 (95 % CI 0.82– 0.88). Subgroup analysis indicated that miRNA assay had higher diagnostic accuracy for relapsing-remitting MS(RRMS) when compared with other MS subtypes. Conclusion: Our study revealed that circulating miRNAs has the potential to be used as diagnostic biomarkers for MS, especially for RRMS. Future studies should clarify to which specific miRNAs can accurately diagnose disease subtypes. The miRNA-related pathogenesis may provide theoretical basis for drug development for early intervention.